Principles of Good Corporate Governance (GCG) in Cash Waqf Management at Cash Waqf Institution - Slamet Haryono; Melis Melis (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2023)
Good Corporate Governance (GCG) is a set of principles and values that aim to optimize the value of a company or organization by ensuring that decision-making and operational processes are carried out in a transparent, accountable, fair, responsible and sustainable manner. The implementation of GCG in waqf bodies is very important to ensure that waqf management is carried out effectively and efficiently so that it can provide maximum benefits for people in need. Following are some of the mechanisms for implementing GCG in waqf bodies: 1) Formation of GCG Committees Waqf bodies can establish a GCG Committee whose job is to develop GCG policies and procedures in accordance with GCG principles. 2) Transparency and Accountability The waqf agency must ensure that all activities and operations carried out are open and transparent, so as to minimize the risk of conflict of interest and corruption. 3) Formation of a Code of Ethics The waqf agency must have a Code of Ethics that regulates the behavior of all parties involved in waqf activities. 4) Training and Education Waqf bodies must provide training and education to all employees, management, and parties related to waqf activities to increase understanding and awareness of GCG principles and how to implement them within the organization. 5) Internal Evaluation and Audit Waqf bodies must conduct regular evaluations and internal audits to ensure that the implementation of GCG in waqf bodies is running well. By applying GCG principles consistently and effectively, waqf bodies can improve their performance and credibility, so that they can gain the trust of the public and provide maximum benefits for people in need.